1995
DOI: 10.1093/treephys/15.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in rooting ability of loblolly pine cuttings: effects of auxin and family on rooting by hypocotyl cuttings

Abstract: After about 20 days, hypocotyl cuttings from 20-day-old loblolly pine (Pinus taeda L.) seedlings rooted easily in the presence of the auxin indole-3-butyric acid (IBA), with roots forming directly from xylem parenchyma. In contrast, woody cuttings from 1-2-year-old hedged seedlings formed roots indirectly from callus tissue in 60-90 days, but IBA had little effect on rooting. Variation in rooting among hypocotyls from both half- and full-sib families was highly significant in response to IBA, and rooting did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 13 publications
(16 reference statements)
3
19
0
1
Order By: Relevance
“…Previous researches of rooting ability of cuttings in conifer and other plants revealed that rooting ability of cuttings were affected by auxin and its family members (Greenwood and Weir, 1994;Syros et al, 2004;Wiesman et al, 1989). The ability of auxins to stimulate adventitious root formation is well documented (Hartmann and Kester, 1983;Sircar Chatterjee, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches of rooting ability of cuttings in conifer and other plants revealed that rooting ability of cuttings were affected by auxin and its family members (Greenwood and Weir, 1994;Syros et al, 2004;Wiesman et al, 1989). The ability of auxins to stimulate adventitious root formation is well documented (Hartmann and Kester, 1983;Sircar Chatterjee, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with hypocotyl cuttings have been developed in conifers (Greenwood and Weir 1994), and could be a useful approach in order to avoid the effect of age, using progenies as cutting donors. More research is necessary to study also the influence of the environmental factors on the rooting process and to adjust practical methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…provenance, family, individual) is largely relevant in determining the rooting behavior within a species (Ying and Bagley 1977, Greenwood and Weir 1994, Dick et al 1996, Stankova and Panetsos 1997, Shoemake et al 2004. As an example, individual differences in the rooting capacity of Cupressus sempervirens L. ranged from 7 to 81% for one same set of experimental conditions (Stankova and Panetsos 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Propagation of the genus Pinus by rooting cuttings obtained from young buds is carried out to multiply progeny identified as superior, in order to obtain elite clones for reforestation and commercial plantations (Greenwood & Weir, 1994;Mori, Miyahara, Tsutsumi, & Kondo, 2011;Zobel & Talbert, 1984). A sexual seed orchard located in Montecillo, State of Mexico, has progeny of some families of Pinus leiophylla Schiede ex Schltdl.…”
Section: Introductionmentioning
confidence: 99%
“…La propagación del género Pinus por medio del enraizado de estacas, a partir de brotes juveniles, se realiza con el propósito de multiplicar progenies identificadas como superiores, a fin de obtener clones élite para reforestación y plantaciones comerciales (Greenwood & Weir, 1994;Mori, Miyahara, Tsutsumi, & Kondo, 2011;Zobel & Talbert, 1984). En un huerto semillero sexual, ubicado en Montecillo, Estado de México, se cuenta con progenie de algunas familias de Pinus leiophylla Schiede ex Schltdl.…”
Section: Introductionunclassified